EFL teachers' experiences of student engagement in synchronous online classes in Oman: Challenges and strategies - Busaidi, Amna Khamis Muftah Al; Dydowicz, Jaroslaw (International Journal of Educational Technology and Learning, 2025)
This study investigates the experiences of Omani school EFL teachers in engaging students during synchronous online classes. Although the data were collected during the COVID-19 pandemic, the findings remain relevant to both current and future online teaching in Oman and similar educational settings. The aim of the study is to identify the key challenges faced by teachers and the strategies they employed to enhance student engagement. A qualitative case study approach was adopted. It involved six female EFL teachers from Cycle Two and Post Basic schools. Data were gathered using semi-structured interviews and a focus group discussion. Through thematic analysis, the research identified several challenges, including technical difficulties, limited face-to-face interaction, low student motivation, cultural and environmental factors, and a misalignment between the curriculum and online learning environments. In response, teachers implemented various strategies, such as the integration of diverse digital tools, the use of motivational techniques, collaborative activities, the promotion of critical thinking, and consistent student monitoring. The findings provide valuable insights into the pedagogical realities of Omani EFL teachers and underscore the ongoing importance of student engagement in virtual learning. This study contributes to the growing body of research on digital education in Oman and calls for continued innovation in teaching practices and sustained professional support for educators working in digital environments.